Maintaining A Temporary Mechanical Circulatory Support Program During A Year of COVID-19 Pandemic - Alonso-Fernandez-Gatta, Marta; Diego-Nieto, Alejandro; Merchan-Gomez, Soraya; Gonzalez-Cebrian, Miryam; Toranzo-Nieto, Ines; Barrio, Alfredo; Martin-Herrero, Francisco; Sanchez, Pedro L (Cardiology and Cardiovascular Medicine, 2022)
Background: The Coronavirus disease 19 (COVID-19) pandemic has impacted clinical practice with important changes in the most affected areas, resulting in increased mortality from heart disease (myocardial infarction). Our objective was to analyze the feasibility of continuing a temporary mechanical circulatory support (MCS) program survival during COVID-19 pandemic. Methods: Retrospective study including all veno-arterial extracorporeal membrane oxygenation (VA-ECMO) and Impella CP® implants in a referral hospital since March 2020 to February 2021. They were compared to previous implants results. Results: Out of 175 short-term MCS implanted from 2013, 33 (18.9%) were conducted during the time of COVID-19 pandemic: 24 VA-ECMO and 9 Impella CP®. Compared to preCOVID-19 implants, patients in COVID-19 era presented worst left ventricular ejection fraction (16.5 [21]% vs 25 [21]%, p=0.018), more frequently right ventricular dysfunction (72.7% vs. 48.6%, p=0.022), without other significant differences regarding the baseline situation and implant technique. Post anoxic encephalopathy was more frequent in COVID-19 era. Survival at discharge was similar in the pre-COVID era (43.7%) and during pandemic (39.4%) (p=0.700). Conclusions: Survival after temporary MCS did not get worse significantly during the COVID-19 pandemic. The possibility of short-term MCS should be maintained for cardiogenic shock and other cases of hemodynamic instability.